A Dual-Layer Control System for Steering Stability of Distributed-Drive Electric Vehicle - Xianghui Xiao; Zhenshan Zhang; Mingxian Huang; Luchang Guan; Yunhao Song; Junbin Zeng (World Electric Vehicle Journal)
In addressing the limitations of traditional steering stability control strategies applied to distributed-drive electric vehicles (DDEVs)—which primarily focus on measuring yaw rate and sideslip angle and may result in loss of control during steering maneuvers—this study conducts a more comprehensive analysis of DDEVs’ steering control stability. It specifically investigates the relationships among the lateral positions of both the front and rear wheels, the slip ratios, and the angular orientation of the vehicle’s body during steering processes. Furthermore, a dual-layer steering stability control system aimed at enhancing the steering stability performance of DDEVs is introduced. This control system consists of two components: a lateral controller and a longitudinal controller. The lateral controller aims to establish clear linkages among four key variables, the front and rear wheel sideslip angles, yaw rate, and sideslip angle, and then to compute the necessary active front wheel steering angle and corresponding yaw moment based on the current vehicle body attitude. The findings indicate that, in comparison to the conventional DDEV controller, the proposed two-layer controller achieves substantially closer alignment to the reference curve during steering, with the accuracy increased by a factor of approximately 5 to 20. These results unequivocally affirm the efficacy and viability of the proposed approach.